Choosing the route of drug administration for hormone therapy of the menopausal period– when is it worth to truck tablets for patches? - Pertyński, Tomasz; Stachowiak, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2006)
The choice of proper way of hormone administration in menopausal women is a crucial element of so-called tailored therapy. In this context transdermal hormone therapy in the form of patches, passing round portal circulation and maintaining stable 17b-oestradiol levels, is an optimal treatment for many clinical states of affairs. The above article presents these cases where transdermal hormonal patches seem to be more suitable than tablets for women in the menopausal period.